Healthy lifestyle in low-socioeconomic groups: expert views - Liza A. Hoveling; Manna A. Alma; Jeanet A. Landsman-Dijkstra; Nynke Smidt; Sijmen A. Reijneveld; Ute Bültmann; Marlou L. A. De Kroon (Frontiers in Public Health)
BackgroundLow socioeconomic position (SEP) increases the risk of health inequalities. Understanding how to realize lifestyle improvements in groups with low SEP may offer routes to reduce these inequalities, and information from professionals involved in this target can support this. Our aims were to gain insight into the professionals’ perspectives on factors that influence the lifestyle of individuals with low SEP, and to identify promising approaches to reduce health inequalities.MethodsFocus group interviews and semi-structured interviews were conducted with 28 social workers (partially in training), health care and policy professionals. All interviews were audio recorded, transcribed verbatim, and analysed following thematic analysis.ResultsFour themes emerged from the data: individual factors, accumulating problems, social context and societal factors; for the second aim a fifth theme emerged: involvement of individuals with low SEP. Participants also indicated a hierarchy in these themes. Addressing accumulating multi-faceted issues such as poverty is imperative before a more healthy lifestyle can be adopted and individuals can focus on skills needed to achieve a healthy lifestyle. Additionally, the social context (e.g., parents or neighbours) can play a supportive role in lifestyle change, supported by government and with active involvement of low SEP individuals.ConclusionAccording to the professionals, to help individuals with low SEP to realize a healthier lifestyle, poverty, knowledge and skills, and the involvement of a person’s social context and society should be addressed.